(3GdhUhd dMaX GdUMI aj GdaUhds - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aUd GdaUhd HMQcGJ GdTeS , hLYd GdLSO eOjfI dedc GdfaS hQHeG cGfJ Ydhe GdCHOGf dZjQgeG CUhdG s
(3BNQgG (B:s
(3gPG eGhSY GdEJjGf Hg Ydi LgI GdGNJUGQ hGdEdeGY , hGdMeO ddg hfSCdg JYGdi Cf jfaY Hg hjLYdg ef CSHGH MSf LRGFg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3aQZ GdeDdas
(3ef JCdjag Sfg (B771(3g`s
(3hgh jTJed Ydi LRAjf (B: (3GdJYQja hGdJUQja hcd eG jTJed Ydi KdGK bhGYO hNGJeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
GAL - (3GdLRA (B2 - (3U (B373 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B282 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B256 s
Keywords: (3GdWHs